2012
DOI: 10.1007/s00467-012-2275-9
|View full text |Cite
|
Sign up to set email alerts
|

Masked hypertension is prevalent in children with sickle cell disease: a Midwest Pediatric Nephrology Consortium study

Abstract: Abnormalities in ABP measurements and patterns in children with SCD are prevalent and require more attention from heath care providers. ABPM is a valuable tool in identifying masked hypertension and abnormalities in circadian BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 28 publications
8
41
0
Order By: Relevance
“…Our cohort confirms prior pediatric studies that demonstrate a lack of correlation between hypertension defined by in-clinic BP monitoring and 24 hour ABPM [21, 35]. In addition, our cohort mirrors the results of two prior studies which suggested that SCA patients have a higher prevalence of nocturnal hypertension and lack of nocturnal dipping in pediatric SCA [21, 22]. The prevalence of non-dipping in this SCA study (70 % abnormal SBP dipping and 50 % abnormal DBP dipping) is higher than obese pediatric patients (42 % and 17 % abnormal SBP and DBP dipping) or patients with diabetes (20-40 % abnormal dipping) [36-38].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our cohort confirms prior pediatric studies that demonstrate a lack of correlation between hypertension defined by in-clinic BP monitoring and 24 hour ABPM [21, 35]. In addition, our cohort mirrors the results of two prior studies which suggested that SCA patients have a higher prevalence of nocturnal hypertension and lack of nocturnal dipping in pediatric SCA [21, 22]. The prevalence of non-dipping in this SCA study (70 % abnormal SBP dipping and 50 % abnormal DBP dipping) is higher than obese pediatric patients (42 % and 17 % abnormal SBP and DBP dipping) or patients with diabetes (20-40 % abnormal dipping) [36-38].…”
Section: Discussionsupporting
confidence: 88%
“…Ambulatory blood pressure monitoring (ABPM), which identifies nocturnal hypertension, is superior to casual in-clinic blood pressure monitoring for identifying children at high risk for end-organ damage [20]. Two prior studies have identified a high prevalence of nocturnal hypertension in SCA, yet no data are available to define the association between nocturnal hypertension and eGFR in SCA [21, 22]. Hyperuricemia has been associated with hypertension and cardiovascular events in other diseases but, despite the high prevalence of hyperuricemia in SCA, the association of hyperuricemia and sickle cell nephropathy has not been explored [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…There is little data about hypertension in children suffering from SCD. In a recent study, high frequency of abnormalities in BP measurements was reported [12]. However, hypertension in SCD is difficult to classify and normal values in sickle cell patient require more attention.…”
Section: Discussionmentioning
confidence: 97%
“…However, masked hypertension is common in pediatric SCD and could contribute to SCN pathophysiology [32,33]. These processes are summarized in Figure 1.…”
Section: Pathophysiologymentioning
confidence: 99%